Low dietary protein content alleviates motor symptoms in mice with mutant dynactin/dynein-mediated neurodegeneration. (30th December 2014) - Wiesner, Diana; Sinniger, Jérome; Henriques, Alexandre; Dieterlé, Stéphane; Müller, Hans-Peter; Rasche, Volker; Ferger, Boris; Dirrig-Grosch, Sylvie; Soylu-Kucharz, Rana; Petersén, Asa; Walther, Paul; Linkus, Birgit; et al.
Abstract: Mutations in components of the molecular motor dynein/dynactin lead to neurodegenerative diseases of the motor system or atypical parkinsonism. These mutations are associated with prominent accumulation of vesicles involved in autophagy and lysosomal pathways, and with protein inclusions. Whether alleviating these defects would affect motor symptoms remain unknown. Here, we show that a mouse model expressing low levels of disease linked-G59S mutant dynactin p150 Glued develops motor dysfunction >8 months before loss of motor neurons or dopaminergic degeneration is observed. Abnormal accumulation of autophagosomes and protein inclusions were efficiently corrected by lowering dietary protein content, and this was associated with transcriptional upregulations of key players in autophagy. Most importantly this dietary modification partially rescued overall neurological symptoms in these mice after onset. Similar observations were made in another mouse strain carrying a point mutation in the dynein heavy chain gene. Collectively, our data suggest that stimulating the autophagy/lysosomal system through appropriate nutritional intervention has significant beneficial effects on motor symptoms of dynein/dynactin diseases even after symptom onset.